IDENTIFIKASI KEBERHASILAN KELOMPOK USAHA BERSAMA MASYARAKAT MISKIN DALAM PROGRAM PENGENTASAN KEMISKINAN DI SUMATERA BARAT Studi Kasus : Program Pemberdayaan Fakir Miskin melalui Bantuan Langsung Pemberdayaan Sosial - Yulia Anas (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
This study aims to analyze the success of the implementation KUBE poverty alleviation programs. By using descriptive and quantitative research methods conducted studies on poverty programs that use the model as a group of target media. From research results indicated that KUBE poor communities can not be said good. Only 29.2% KUBE the Advanced category. So that this situation is thought to be the cause of the failure of programs to alleviate poverty.